The Power of Conferences Stories of serendipity, innovation and driving social change - Edwards, Deborah (UTS ePRESS, 2017)
The Power of Conferences: Stories of serendipity, innovation and driving social change asks ten notable Australians to reflect on the role that conferences have played in their personal and professional achievements. Through their stories the power of conferences is revealed, providing evidence of a deep and lasting impact on the development and success of Australian luminaries and their communities. This book arose from a long term collaboration with Business Events Sydney.